2007
DOI: 10.1073/pnas.0702969104
|View full text |Cite
|
Sign up to set email alerts
|

Somatic loss of BRCA1 and p53 in mice induces mammary tumors with features of human BRCA1 -mutated basal-like breast cancer

Abstract: Women carrying germ-line mutations in BRCA1 are strongly predisposed to developing breast cancers with characteristic features also observed in sporadic basal-like breast cancers. They appear as high-grade tumors with high proliferation rates and pushing borders. On the molecular level, they are negative for hormone receptors and ERBB2, display frequent TP53 mutations, and express basal epithelial markers. To study the role of BRCA1 and P53 loss of function in breast cancer development, we generated conditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
440
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 430 publications
(464 citation statements)
references
References 51 publications
20
440
2
2
Order By: Relevance
“…We next determined ROS levels in Brca1-deficient primary MECs (pMECs) using a previously generated Brca1 conditional knockout mouse (B1 f/f ) carrying a cre-inducible deletion of Brca1 exons 5-13 (Liu et al, 2007). Targeted Brca1 deletion to the mammary gland epithelium was achieved by crossing B1 f/f mice to K14cre mice (Jonkers et al, 2001) to obtain K14cre;Brca1 f/f mice (KB1 f/f ) along with K14cre (K) and K14cre;Bf/+ (KB1 f/+ ) control mice.…”
Section: Brca1 Loss-of-function In Mecs Causes Ros Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…We next determined ROS levels in Brca1-deficient primary MECs (pMECs) using a previously generated Brca1 conditional knockout mouse (B1 f/f ) carrying a cre-inducible deletion of Brca1 exons 5-13 (Liu et al, 2007). Targeted Brca1 deletion to the mammary gland epithelium was achieved by crossing B1 f/f mice to K14cre mice (Jonkers et al, 2001) to obtain K14cre;Brca1 f/f mice (KB1 f/f ) along with K14cre (K) and K14cre;Bf/+ (KB1 f/+ ) control mice.…”
Section: Brca1 Loss-of-function In Mecs Causes Ros Accumulationmentioning
confidence: 99%
“…We used a Brca1 conditional knockout mouse (Liu et al, 2007) to specifically delete the Brca1 gene in the mammary gland. Although Brca1 deletion under the control of K14-or K6a-driven cre recombinase does not lead to any observable changes in the mammary gland (Liu et al, 2007;Smart et al, 2011), our study of primary and immortalized mouse and human BRCA1-deficient MECs shows that BRCA1 deficiency results in ROS accumulation in these cells. This effect When we evaluated Nrf2 expression in KB1 f/f pMECs, we found that both mRNA (Fig.…”
Section: Brca1 Loss-of-function In Mecs Causes Ros Accumulationmentioning
confidence: 99%
“…Accordingly, p53 À/À mice, at least in the murine genetic background C57/BL6, rarely develop mammary tumors [34,[36][37][38][39]. Nevertheless, several observations suggest that loss of p53 is involved in the etiopathology of both human and mouse mammary tumors: (i) mutations of p53 are found in many breast cancers and women affected by the Li-Fraumeni syndrome (an inherited predisposition to cancer development linked to germline mutations in the p53 gene) often develop breast tumors [38]; (ii) in the BALB/c background, approximately 75% of p53 À/À mice have microscopic lesions in the mammary gland (sarcomas, epithelial hyperplasia and alterations in stromal morphology) [40]; (iii) transplantation of the p53 À/À BALB/c epithelium into fat pads of WT syngeneic mice leads to the development of mammary carcinomas in 60-75% of mice [40,41]; (iv) in a conditional mammary tumor model, approximately 70% of mice that carry tissue-specific inactivation of p53 develop mammary carcinomas [42]; and (v) in ErbB2 transgenic mice, which develop mammary carcinomas with high penetrance and short latency, p53 impairment is responsible for the immortal behavior and the geometric expansion of mammary CSCs in vitro and for carcinoma growth in vivo [34].…”
Section: Opinionmentioning
confidence: 99%
“…The main type of mammary tumor found in the Apc min/+ Xrcc2 +/− mice was adenocarcinoma with squamous cell differentiation; similarly, this type of tumor was found in Brca1-or Brca2-compromised mice (23,24). These data suggest that Xrcc2 may act as a tumor suppressor following radiation damage, but in parallel to studies of mouse mutants of the Brca genes (25,26), further development of conditional and tissue-specific mouse Xrcc2 mutants would be required to support this finding.…”
Section: Discussionmentioning
confidence: 89%